PWE-087 A Critical Review of Grounded Theory use in Inflammatory Bowel Disease Studies. (4th June 2013) - Fragkos, K C; Forbes, A
Abstract : Introduction: Grounded Theory (GT) is a research methodology predominantly used with qualitative data. The purpose of the present study is to critically evaluate the use of GT in inflammatory bowel disease (IBD) studies and to examine the clinical implications this entails. Methods: A systematic literature review was performed using keywords Grounded Theory and IBD in Pubmed, EMBASE and Scopus with no time limits. Assessment of GT was performed using standard criteria suggested by Glaser (1998). The application of the following basic principles was examined: simultaneous data collection and analysis; construction of analytic codes and categories from data, not from preconceived logically deduced hypotheses; use of constant comparative method; advancement of theory development during each step of data collection and analysis; memo-writing; sampling aimed toward theory construction (theoretical); Literature review after the core category emergence. Results: Fifteen studies have used GT investigating patient education, quality of life, experiences with therapeutic strategies or coping mechanisms in IBD, providing theories based on emerging categories. About half of all studies have applied the basic principles of GT, with the remaining studies being unclear or having not applied them. The most reported priniciple was Glaserian selective coding and least reported were memoing, theoretical sampling and the achievement of theoretical completeness, while the identification of the core category was unclear in many instances (Figure 1). These weaknesses are attributed predominantly to methodological, verification and reporting bias. These biases affect the applicability of these results in clinical practise. Hence, results concerning quality of life or experiences of IBD patients should be treated with caution, as they could represent authors' predisposition from the their experience (empirical or from literature reviews). Conclusion: The main advantage of GT studies remains the generation of theory that can be applied in practise, reinforced by the presentation of conceptual prospects for testing new variables in quantitative studies. Overall, the contribution of Grounded Theory studies to IBD should be based on more rigorous methodology and aim to challenge rather than confirm existing conceptions with the purpose of advancing knowledge in the field. Disclosure of Interest: None Declared. References: Glaser BG, (1998), Doing Grounded Theory: Issues and Discussions, Sociology Press, Mill Valley, CA.